Exhausted and Apoptotic BALF T Cells in Proinflammatory Airway Milieu at Acute Phase of Severe Mycoplasma Pneumoniae Pneumonia in Children - Chen, Xi; Liu, Fang; Zheng, Baoying; Kang, Xiaohui; Wang, Xiaolin; Mou, Wenjun; Zhang, Hui; Jiao, Anxia; Zhao, Shunying; Gui, Jingang (Frontiers in Immunology, 2022)
Severe mycoplasma pneumoniae pneumonia (MPP) in children present with serious clinical complications. Without proper and prompt intervention, it could lead to deadly consequence. Dynamics of the inflammatory airway milieu and activation status of immune cells were believed to be the hallmark of the pathogenesis and progress of the disease. In this study, by employing the T-cell sorting and mRNA microarray, we were able to define the main feature of the chemokine/cytokine expression and the unique characteristics of T cells in the bronchoalveolar lavage fluid (BALF) from severe MPP patients at acute phase. Our study for the first time delineate the molecular changes in isolated BALF T cells in severe MPP children with respect to the cytokines/chemokines expression, cell activation, exhaustion and apoptosis. By comparing the BALF aqueous expression of cytokines /chemokines with that in sorted T cells, our data give a preliminary clue capable of finishing out the possible cell source of the pro-inflammatory cytokines/chemokines from the BALF mixture. Meanwhile, our data provide a distinctively pellucid expression profile particularly belongs to the isolated BALF T cells demonstrating that in the inflammatory airway, over-activated T cells were exhausted and on the verge of apoptotic progress.